A simple and flexible approach for detecting small numbers of SNPs - Yu, Renbo; Liu, Jie; Niu, Yu; Han, Xu; Wang, Xiaoyi; Yang, Yan (Frontiers in Plant Science, 2025)
SNP markers represent the most extensively distributed and abundant type of polymorphic markers. Although researchers have developed high-throughput detection methods for SNP markers, there remains a lack of simple, flexible, and cost-effective approaches for detecting small numbers of SNPs. To address this need, this study proposes a method for detecting SNPs based on T-C mismatch. Specifically, two upstream primers were designed with a single base difference at the 3’ end. Additionally, a T-C mismatch was introduced within 5 bp upstream of the 3’ end to distinguish SNPs. Detection was achieved through PCR amplification and subsequent gel electrophoresis analysis. In this study, twelve random SNPs from bitter gourd were selected, and the detection efficiency was found to be 83.3%. The proposed SNP detection method is characterized by its simplicity and flexibility, offering an effective tool for molecular marker-assisted selection breeding in applications such as stress resistance improvement and agricultural productivity enhancement.